The association between premature rupture of membranes (PROM) and preterm gestational age with neonatal sepsis: a systematic review and meta-analysis - Nanda Andini; Lili Rohmawati; Erjan Fikri; Bugis Mardina (Paediatrica Indonesiana, 2023)
Background Sepsis is one of the main causes of neonatal mortality. The morbidity and mortality rates due to neonatal sepsis are as high as 9-20%. Premature rupture of membranes (PROM) and preterm gestational age are among the risk factors of neonatal sepsis. Objective To evaluate for potential associations between PROM as well as preterm gestational age to neonatal sepsis by meta-analysis and systematic review. Methods A meta-analysis and systematic review were performed using literature sourced from PubMed, Cochrane, and Google Scholar according to PRISMA guidelines. We calculated the incidence of sepsis in neonates with and without PROM and premature gestational age. Journal quality was assessed according to the Newcastle-Ottawa Scale (NOS) criteria. Results From the literature search for PROM, 21 case-control studies met the inclusion criteria. Neonatal sepsis was more common in neonates who had a maternal history of PROM than in those without [OR 2.69 (95%CI 1.56 to 4.65); P<0.00001]. From the literature search for gestational age, we found 17 case-control studies that met the inclusion criteria. Neonatal sepsis was more common in preterm than term neonates [OR 2.55 (95%CI 1.61 to 4.04); P<0.00001]. Conclusion Neonates with a maternal history of PROM and/or preterm gestational age are at high risk of developing neonatal sepsis.